Comparative study of various volcanic materials as fillers in polymer composites - Liubov Melnyk; Lev Chernyak; Valentin Sviderskyy; Ludmila Vovchenko; Viktoria Yevpak (Zaštita Materijala)
The object of the study was composite materials using rocks of volcanic origin as a filler (60-90 wt.%) and aqueous dispersions of polymers Latex 2012 and Policril 590 as a matrix. The peculiarities of the chemical and mineralogical composition and surface properties of perlite and zeolite as factors of interaction with the binder in the formation of the composite structure are shown. Differences in lyophilicity coefficients and effective specific surface of zeolite and perlite were determined, which are 0.318 versus 0.189 and 11.68 versus 2.20 m2/g, respectively. The influence of a high concentration of fillers on the formation of the pore structure and indicators of physical and mechanical properties of composites is evaluated. The possibility of adjusting the properties of the composites in the following range was established: water absorption in the range of 2.63-14.16 wt.%, open porosity 3.58-21.35 %, residual strain 0.1-0.3, Young’s modulus 19.7-677.5 MPa.